Mass media in the economic development of Belarusian regions - Korshuk, Victoria V. (Journal of the Belarusian State University. Journalism, 2024)
The author reveals the potential of the press in the economic development of the Belarusian regions. The results of the analysis of 22 publications of the republican, regional, district, and city levels are presented for the content compliance with the actual needs of the territories. The reviewed experience of the national press will allow re-evaluating and adjusting the information strategies of the regional media.